Variantes del gen CFTR en pacientes con diagnóstico de fibrosis quística de la Fundación Fundafiq Cuenca-Ecuador - Flores García, Mónica Susana (2020)
Cystic Fibrosis is an autosomal recessive disease caused by loss of function variants in the CFTR gene. Knowing the genetics of the disease is difficult, because at present more than 2000 different genetic variants have been described, which cause variable phenotypes with great clinical heterogeneity, whose incidence varies in the population according to their geographical and ethnic origins. The aim of this study was to identify the variants of CFTR gene in patients with Cystic Fibrosis from Fundafiq Foundation in Cuenca city. A descriptive and transversal observational study was carried out based on the review of Fundafiq and Vicente Corral Moscoso Hospital clinical records. It was identified a group of 9 patients with molecular analysis, finding the following variants, whose frequencies were F508del 4, N1303K 4, H609R 3, G85E 2, c.2672del 2, W496R 2 and L15P 1. In the analysis of the family tree it was found consanguinity in 4 patients and family history in six patients. In conclusion, the results of this study show that the most frequently identified variants were F508del, N1303K and H609R. It was identified a new variant the W496R not reported in other populations, which is relevant in the knowledge of the spectrum of variants in the population of Ecuador.